POTENTIAL EFFECTS OF BOVINE COLOSTRUM IN PREVENTION OF NECROTIZING ENTEROCOLITIS: A REVIEW - Aleksandra Przybylska; Julia Ciechanowicz; Stanisław Ciechanowicz; Julia Dura; Marika Gutowska; Piotr Kupidłowski; Agata Nowacka; Adrianna Perzanowska; Zuzanna Tomaszewska; Anna Zielińska (International Journal of Innovative Technologies in Social Science, 2025)
Objectives: Necrotizing enterocolitis is a critical gastrointestinal disorder predominantly affecting neonates. Bovine colostrum is a nutrient-dense first secretion from cows postpartum. Bovine colostrum is abundant in immunoglobulins, antimicrobial peptides as well as growth factors, making it a promising candidate for nutritional intervention for necrotizing enterocolitis. This review aims to critically assess the existing preclinical and clinical evidence on the efficacy of bovine colostrum supplementation in reducing the incidence and severity of necrotizing enterocolitis in neonatal populations. Methods: A literature search was conducted using PubMed and Scopus databases. Relevant animal trials and human randomized controlled trials evaluating the impact of bovine colostrum on necrotizing enterocolitis incidence and severity were analysed. Key findings: Preclinical studies in neonatal piglet models consistently demonstrate that bovine colostrum reduced the incidence and severity of necrotizing enterocolitis compared to infant formula, with mechanisms involving enhanced gut barrier integrity, microbiota modulation and reduction in inflammation. Bovine colostrum outcomes were often comparable or superior to human donor milk. However, recent randomised controlled trials in preterm human infants have not shown a statistically significant reductions in necrotizing enterocolitis incidences with bovine colostrum supplementation, possibly due to differences in product processing, dosage and open-label study designs. Conclusions: Despite promising outcomes in zootechnical models, current clinical evidence does not confirm efficacy of bovine colostrum in necrotizing enterocolitis prevention in human neonates. Further high-quality, standardized, double-blinded clinical trials are needed to clarify its potential in infant care.